Efektivitas Layanan Bimbingan Kelompok Melalui Diskusi Kelompok Dalam Meningkatkan Kemampuan Mengelola Emosi Remaja - Fadlilah, Alif Nurul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the effectiveness of group counseling services through group discussion techniques in enhancing adolescents’ emotional regulation skills. The research employed a pre-experimental approach using a one-group pretest-posttest design. The sample consisted of 10 students selected purposively based on a high need for emotional management. The instrument used was an emotional regulation questionnaire that had been tested for validity and reliability. Data were analyzed using paired sample t-test to determine the difference between pretest and posttest scores. The results showed an increase in the average score from 59.80 to 75.40 after the intervention. The t-test indicated a significance value of 0.000 0.05, confirming a significant difference before and after the service. These findings suggest that group discussion techniques within group counseling are effective in significantly improving adolescents’ emotional regulation abilities.